A techno-economic analysis of EU renewable electricity policy pathways in 2030. (May 2017) - del Río, Pablo; Resch, Gustav; Ortner, Andre; Liebmann, Lukas; Busch, Sebastian; Panzer, Christian
Abstract: The aim of this paper is to assess several pathways of a harmonised European policy framework for supporting renewable electricity (RES-E) in a 2030 horizon according to different criteria. The pathways combine two main dimensions: degrees of harmonisation and instruments and design elements. A quantitative model-based analysis with the Green-X model is provided. The results of the simulations show that there are small differences between the evaluated cases regarding effectiveness. All the policy pathways score similarly with respect to RES-E deployment, i.e., with different degrees of harmonisation and whether using a feed-in tariff, a feed-in premium, a quota system with banding or a quota without banding scheme. In contrast, the policy costs clearly differ across the pathways, but the differences can mostly be attributed to the instruments rather than to the degrees of harmonisation. This is also the case with other criteria (static and dynamic efficiency and the socioeconomic and environmental benefits in terms of CO2 emissions and fossil fuels avoided). Both the degree of harmonisation and the choice of instrument influence the distribution of support costs across countries. Finally, our findings suggest that keeping strengthened national support leads to similar results to other policy pathways. Highlights: Pathways of a harmonised European policy framework for renewable electricity in 2030. Two main dimensions: degrees of harmonisation and instruments. A quantitative model-based analysis based on the Green-X model. Small differences between the pathways regarding the effectiveness criterion. Important differences between pathways regarding other assessment criteria.